The Importance of Employee Performance of Civil Servant in Near-Retirement Phase at Pemalang Residence - Putranti, Honorata Ratnawati Dwi; Tyoso, Jaluanto Sunu Punjul; Ismiyarto, Ismiyarto (Research and Development Agency Ministry of Home Affairs, 2018)
The aim of this research was to find a management model for the civil servant in approaching the retirement (near-retirement phase). The retirement period experienced by each person at the end of his/her working period is expected to provide comfort for the next life. The research applied case study design with qualitative approach. The interview was conducted in depth (in-depth interview) in which the informants were the civil servants in the Regional Secretariat of Pemalang District. The data credibility was carried out by using data triangulation. The findings of this research indicated that the internal social relationship of male employees towards retirement was more active than female employees. Moreover, male employees cared more about health factors than female employees. Male employees took more time before retirement whereas female employees were women are more sincere. In addition, they needed social support on the eve of retirement such as financial preparation, role adjustment and retirement activities. Family and colleague’s support was the most important support needed before retirement